Salivary melatonin rhythm as a marker of the circadian system in healthy children and those with attention-deficit/hyperactivity disorder - Nováková, Marta; Paclt, Ivo; Ptáček, Radek; Kuželová, Hana; Hájek, Ivan; Sumová, Alena (Chronobiology international, 2011)
Attention-deficit/hyperactivity disorder (ADHD) is the most common neurobehavioral disorder of childhood. Problems with sleep structure, efficiency, and timing have been reported in some, but not all, studies on ADHD children. As the sleep-wake cycle belongs to circadian rhythms, the timekeeping circadian system might be involved in ADHD. To assess whether the circadian system of ADHD children differs from that of controls, the rhythm of the pineal hormone melatonin was used as a reliable marker of the system. Saliva from 34 ADHD and 43 control 6- to 12-yr-old children was sampled at 2-h intervals throughout the entire 24-h cycle, and the melatonin profiles of the ADHD and control children were compared. The nocturnal melatonin peaks of the ADHD and control group did not differ significantly. The high nocturnal interindividual variability of the peaks seen in adulthood was present already in the studied children. The 24-h melatonin profiles of all the ADHD subjects did not differ significantly from those of the control subjects. Categorization of subjects according to age, into groups of 6- to 7-yr-old (9 ADHD, 5 control), 8- to 9-yr-old (16 ADHD, 26 control), and 10- to 12-yr-old (9 ADHD, 12 control) children, revealed significant differences between the ADHD and control group in the melatonin rhythm waveform, but not in nocturnal melatonin peaks; the peaks were about the same in both groups and did not change significantly with increasing age. In the oldest, but not in the younger, children, the melatonin signal duration in the ADHD group was shorter than in the control group. The difference might be due to the fact that whereas in the control group both the evening melatonin onset and the morning offset phase delayed in the oldest children relative to those in the youngest children, in the ADHD group only the onset, but not the offset, phase delayed with increasing age. The data may indicate subtle differences between the circadian system of ADHD and control children during development.
Keywords: dítě; biologické markery; Česká republika; Melatonin; sliny; lidé; Attention Deficit Disorder with Hyperactivity; Czech Republic; Circadian Rhythm; Saliva; radioimunoanalýza; Female; cirkadiánní rytmus; Biomarkers; Male; ženské pohlaví; Humans; Child; mužské pohlaví; Radioimmunoassay; melatonin; hyperkinetická porucha